(untitled) (Applied Biological Research, 2018)
Electrocardiogram (ECG) of 49 healthy male goats (Capra hircus) was recorded in three bipolar standard leads (lead I, II and III) and three augmented unipolar limb leads (aVR, aVL and aVF). Taking the different ECG values of all the leads into consideration, the amplitude of P wave ranged from 0.04 mV to 0.15 mV while the P wave in the lead aVR was found to be inverted in all the cases and the mean value was measured to be 0.1 ± 0.02 mV. The duration of P wave ranged from 0.02 to 0.06 sec. The R wave amplitude ranged from 0.35 mV to 0.8 mV and the maximum numbers of upright R waves were traced in lead II, III and aVF while lead I and aVL showed inverted R wave in all the cases. The amplitude of T wave ranged from 0.1 to 0.3 mV. The P-R interval ranged from 0.04 to 0.30 sec. The QT interval varied between 0.18 and 0.36 sec while the R-R interval ranged from 0.44 to 0.84 sec. The heart rate varied from 80 to 130 beats min-1.